PENGARUH KOMPETENSI PROFESIONAL GURU DAN FASILITAS SEKOLAH TERHADAP HASIL BELAJAR SISWA SMK - Gilly Marlya Tiwow; Intan Christina Pudi; Devyano V.F. Ranti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Students’ learning outcomes represent an important indicator in assessing the success of the educational process, which is influenced by various factors, particularly teachers’ competence and the availability of school facilities. This study aims to analyze the effect of teachers’ professional competence and school facilities on students’ learning outcomes at SMK Negeri 1 Bolaang. The research employed a quantitative approach using a survey method with an explanatory research design that emphasizes testing causal relationships among variables. Data were collected through observation, questionnaires, and documentation involving 125 students as respondents. The research instruments were tested for validity and reliability to ensure the accuracy and consistency of the data obtained. Data analysis was conducted using regression techniques to examine both partial and simultaneous effects of the variables. The results indicate that teachers’ professional competence and school facilities individually have a positive and significant effect on students’ learning outcomes (p < 0.05), with a coefficient of determination (R²) of 0.798. Furthermore, both variables simultaneously have a significant effect on learning outcomes, as indicated by an F-value of 107.023, which exceeds the F-table value. The significance level of < 0.05 suggests that teachers’ professional competence and school facilities are key determinants in improving students’ learning outcomes. Therefore, enhancing teachers’ professional competence supported by adequate school facilities is an effective strategy to improve the quality of learning and students’ academic achievement. ABSTRAK Hasil belajar siswa merupakan indikator penting dalam menilai tingkat keberhasilan proses pendidikan yang dipengaruhi oleh berbagai faktor, terutama kompetensi guru dan ketersediaan fasilitas sekolah. Penelitian ini bertujuan untuk menganalisis pengaruh kompetensi profesional guru serta fasilitas sekolah terhadap hasil belajar siswa di SMK Negeri 1 Bolaang. Penelitian ini menggunakan pendekatan kuantitatif melalui metode survei dengan desain explanatory research yang menekankan pada pengujian hubungan kausal antarvariabel. Data dikumpulkan melalui observasi, penyebaran angket, dan dokumentasi dengan melibatkan 125 siswa sebagai responden. Instrumen penelitian telah melalui uji validitas dan reliabilitas guna memastikan akurasi serta konsistensi data yang diperoleh. Analisis data dilakukan menggunakan teknik regresi untuk menguji pengaruh variabel baik secara parsial maupun simultan. Hasil penelitian menunjukkan bahwa kompetensi profesional guru dan fasilitas sekolah secara parsial memiliki pengaruh positif dan signifikan terhadap hasil belajar siswa (p < 0,05), dengan nilai koefisien determinasi (R²) sebesar 0,798. Selain itu, secara simultan kedua variabel juga berpengaruh signifikan terhadap hasil belajar, yang ditunjukkan oleh nilai F-hitung sebesar 107,023 yang lebih tinggi dibandingkan F-tabel. Nilai signifikansi < 0,05 mengindikasikan bahwa kompetensi profesional guru dan fasilitas sekolah merupakan faktor determinan dalam meningkatkan hasil belajar siswa. Oleh karena itu, peningkatan kompetensi profesional guru yang didukung oleh penyediaan fasilitas sekolah yang memadai menjadi strategi